Development of a competency framework for Palliative Care Nurses at Maharaj Nakorn Chiang Mai Hospital and eight Network Hospitals in Northern Thailand. - ใจเปี้ย อัมภวรรณ์; บัวชุม อุบล; ชมพูแก้ว พายุรี (Journal of Nurses Association of Thailand Northern Office, 2018)
The purpose of this developmental study was to develop an appropriate competency framework of palliative care for nurses working at Maharaj Nakorn Chiang Mai hospital and 8 network hospitals in northern Thailand, by applying the strategy for developing competency model by Marrelli, Tondora, &Hoge. The samples consisted of 20 nurse-palliative care specialists and a panel of 5 experts chosen by purposive sampling. The research instrument was an interview guideline validated by 3 experts. Data collection included: 1) reviewing the relevant literatures, 2) interviewing 6 nurse-midwife specialists, 3) developing the first draft of competency framework, and 4) validating e a draft by a panel of 5 experts (I-CVI) = 1 The results of this study revealed that a competency framework for palliative care nurses , at Maharaj Nakorn Chiang Mai hospital and 8 network hospitals in Northern Thailand, consisted of 10 components ; 1) communication 2) pain assessment and management 3) symptom assessment and management 4) attitude of caring 5) ethics and legal issues 6) religion and believes 7) last days/ hours/imminent death care 8) loss, grief and bereavement support 9) inter professional / collaborative practice and 10) professional development and advocacy. It is suggested that nurse administrators could use this competency framework as a guideline for developing an assessment tool for measuring specific competency of palliative care nurse.